Continuing care unit: new therapeutic and care solution in terminal illness - Turriziani, Adriana; Nardone, Luigia; Spedicato, Maria Rosaria; Scopa, Anna Maria; Marmiroli, Luca (Medicina e Morale, 1988)
Continuing Care Unit (C.C.U.) is a program of care that integrates inpatient care (outpatient, inpatient and day hospital) with home care, when the latter due to the severity or complexity of the disease cannot be implemented by the family physician alone.